The Activity of Older People Determining Their Functional Abilities During Old Age: A Cross-Sectional Study in Two Major Cities In Indonesia - Bondan Palestin; Siti Nur Kholifah; Yessy Dessy Arna; Tantut Susanto; Amalia Mufid Fadhila (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Amidst Indonesia's aging population, this study explores key determinants influencing productivity, the indicators of functional abilities, among older adults in diverse urban/rural settings of East Java and Yogyakarta. The study design used a cross-sectional study surveyed 220 adults (≥60 years; mean age 65.3) via stratified probability sampling. Structured questionnaires assessed holistic health (biological, psychological, social, spiritual, cultural), active ageing determinants (social, habitual, physical, personal, economic, service access), and elderly capability improvement (physical, mental, social, spiritual, cultural health). Binary logistic regression identified predictors of productivity status. The study results showed that holistic health conditions (Exp(B) = 0.983, p = 0.050), active ageing determinants (Exp(B) = 1.16, p =0.000), and improvements in elderly capabilities (Exp(B) = 1.090, p = 0.005) were significant positive predictors of productivity. This Indonesian study demonstrates that specific active ageing determinants and enhanced capabilities are more critical to elderly productivity than general holistic health in a multivariate context. It highlights the need for targeted, regionally adaptable community interventions and age-friendly policies to support productive aging.